Mayor Hubble is in trouble! - Gutman, Dan (Gutman, Dan. My weirder school, 2012)
Election day is right around the corner, and guess who's running for class president? A.J. and Andrea! Mayor Hubble is going to teach the kids all the ins and outs of politics, and every vote counts. Who's going to win? Who's going to lose? And who's going to kiss a baby? Ew, gross!